2021
DOI: 10.1016/j.clnu.2020.10.026
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a duodenal-jejunal bypass liner on lipid profile and blood concentrations of long chain polyunsaturated fatty acids

Abstract: Background & aims: Duodenal-jejunal bypass liners (DJBLs) prevent absorption in the proximal small intestine, the site of fatty acid absorption. We sought to investigate the effects of a DJBL on blood concentrations of essential fatty acids (EFAs) and bioactive polyunsaturated fatty acids (PUFAs). Methods: Sub-study of a multicentre, randomised, controlled trial with two treatment groups. Patients aged 18e65 years with type-2 diabetes mellitus and body mass index 30e50 kg/m 2 were randomised to receive a DJBL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 54 publications
1
28
0
Order By: Relevance
“…Several other studies that have examined plasma NEFA profiles in patients after various types of bariatric surgery have found such interventions to lead to significant reductions in total NEFA concentrations (and groups of fatty acids) in the months following surgery 28 33 , in a manner similar to that observed in this study. A meta-analysis published in 2016 found that serum NEFA levels were decreased at 6 and 12 months but did not differ from preoperative levels at 3 months post-surgery 34 .…”
Section: Resultssupporting
confidence: 81%
“…Several other studies that have examined plasma NEFA profiles in patients after various types of bariatric surgery have found such interventions to lead to significant reductions in total NEFA concentrations (and groups of fatty acids) in the months following surgery 28 33 , in a manner similar to that observed in this study. A meta-analysis published in 2016 found that serum NEFA levels were decreased at 6 and 12 months but did not differ from preoperative levels at 3 months post-surgery 34 .…”
Section: Resultssupporting
confidence: 81%
“…Similarly, for the other cardiometabolic risk factors such as blood pressure, EFAs, total cholesterol, and LDL cholesterol, Laubner et al ( 40 ) and Glaysher et al ( 38 ) both showed significant decreases in the DJBL group vs. the SMT group. However, Caiazzo et al ( 39 ) found that there was no significant difference in BMI loss, HOMA2, blood pressure, HDL cholesterol and triglycerides after removal of DJBL.…”
Section: Resultsmentioning
confidence: 88%
“…Four randomized controlled trials and one case control study investigated the effects of DJBL on weight loss ( Table 5 ). Large-sample randomized controlled trials (of 170 participants each) conducted by Ruban et al ( 37 ) and Glaysher et al ( 38 ) both showed significantly greater TBWL in the DJBL group vs. SMT group, Three studies comprising 510 participants ( 21 , 38 , 40 ) studied change in BMI between the DJBL and SMT group at 6 months ( Figure 2D ). Our analysis showed no significant reduction in BMI between the DJBL and SMT group (WMD −2.73 (−5.52, 0.07) kg/m 2 )).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Thus, DPA affected colon motility and induced constipation only when applied through the colon in vitro but not through diet. This may be due to the fact that, similar to other PUFAs, dietary DPA is absorbed thoroughly in the small intestine ( 26 ). It is plausible that the fecal DPA we detected in the IFC patients was primarily produced by PIB in the colon rather than by food intake.…”
Section: Discussionmentioning
confidence: 99%